Pengaruh Kinerja Auditor, Turn Over Intention, dan Komitmen Organisasi terhadap Premature Sign-Off - Mindarti, Ceacilia Sri; Puspitasari, Elen (Widya Mandala Surabaya Catholic University, 2012)
This research aims to analyze the i4fluence of auditor individual performance, Turnover intention, and organizational commitment to premature sign-off. Goal Setting Theory in this study is used to review and analyze the influence o j internal individual factors (such a s auditor individual performance, turnover intention and organizational commitment on acceptance of a premature sign-off. Source o f data in this study w ere auditors working in audit firms in Indonesia a s respondent The data was collected using survey method b y sending questionnaires to the respondents by mail. The result of the study has shown that individual performance, turnover intention and organizational commitment have influence to acceptance of a premature sign-off.